The Influence Of Enterpreneur Perceptions And The Use Of Accounting Prosedures On The Success Of Small And Medium Enterprise At Gallon Water Refill Depots Selebar District Bengkulu City - Muhamad Rama Fitra Buana; Ahmad Soleh; Rinto Noviantoro (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
The purpose of this study was to analyze the influence of entrepreneur perceptions and the use of accounting procedures on the success of Small and Medium Enterprise at gallon water refill depots, as wide as Bengkulu City. This type of research is descriptive qualitative. Data collection techniques using a questionnaire. The analytical method used is the Validity test using the SPSS (Statistical Product and Service Solusions) version 25.0 program which can be done by looking at the correlation between the scores of each item in the questionnaire. The results of this study indicate that the coefficient of determination of the R square value is 0.096. This means that X1 (Entrepreneur's Perception) and X2 (Accounting Procedures) have a positive effect on (Business Success) Y. but is not significant.